2016
DOI: 10.1177/1363459316649764
|View full text |Cite
|
Sign up to set email alerts
|

Obesity frames and counter-frames in British and German online newspapers

Abstract: By featuring news articles highlighting certain aspects of obesity and backgrounding others, the media can frame these aspects as especially applicable to how obesity should be understood and addressed. Despite the highest rates in Europe, news reports from Britain and Germany have come under little scholarly scrutiny. In this article, we explore frames and their frequency of use in British and German online newspapers. Our findings reveal a dominant cross-national framing of obesity in terms of 'self-control'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 52 publications
(73 reference statements)
0
26
0
2
Order By: Relevance
“…In contrast, Hawamdeh et al. have reported that the prevalence of depression, as a comorbidity of T2DM among Arab women in Arab countries, is very significant 31 . Additionally, a local study has also shown that unmarried patients were three times more depressed than married patients 10 …”
Section: Discussionmentioning
confidence: 93%
“…In contrast, Hawamdeh et al. have reported that the prevalence of depression, as a comorbidity of T2DM among Arab women in Arab countries, is very significant 31 . Additionally, a local study has also shown that unmarried patients were three times more depressed than married patients 10 …”
Section: Discussionmentioning
confidence: 93%
“…Even in the case of lung cancer related to a history of tobacco use, patients are usually seen as victims trapped by their addictions. If a medical classification can help to reduce the persistent weight bias narrative in the mainstream media and social media , this is also a compelling justification for the World Obesity position.…”
Section: Supporting Treatmentmentioning
confidence: 99%
“…Typically, framing promotes "a particular problem definition, causal interpretation, moral evaluation and/or treatment recommendation" for the issue at hand (Entman, 1993, p.52). For example, the framing of obesity in news coverage was found to shift between the attribution of moral responsibility to obese persons, the faulting of social and economic forces, the promotion of education for life-style changes or the rejection of the medicalization of obesity altogether (Lawrence, 2004;Atanasova & Koteyko, 2016). By implying the cause and accountable persons, each frame suggests different recommendations or policies each targeting in the main citizens, health authorities or industry (Khayatzadeh-Mahani, Ruckert, & Labonté, 2017).…”
Section: Framing Health Risksmentioning
confidence: 99%